2006
DOI: 10.1093/annonc/mdl958
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of TP53, Ki-Ras and p16INK4A promoter methylation in plasma of patients with colorectal cancer and its association with prognosis. Results of a 3-year GOIM (Gruppo Oncologico dell'Italia Meridionale) prospective study

Abstract: Detection of Ki-Ras and TP53 mutation in plasma should be significantly related to disease recurrence. These data suggest that patients with a high risk of recurrence can be identified by means of the analysis of tumor-derived plasma DNA with the use of fairly non-invasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…In the study published by Bazan et al, it was shown that the preoperative detection of mutant KRAS and TP53 in the serum of CRC patients undergoing resective surgery, was predictive of disease recurrence [65]. In another study it was detected the amount of circulating tumor DNA in 18 MCRC patients who underwent surgical resection of their metastases and it was observed that the detection of circulating mutant DNA after surgery was highly predictive of disease recurrence [66].…”
Section: Colorectal Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In the study published by Bazan et al, it was shown that the preoperative detection of mutant KRAS and TP53 in the serum of CRC patients undergoing resective surgery, was predictive of disease recurrence [65]. In another study it was detected the amount of circulating tumor DNA in 18 MCRC patients who underwent surgical resection of their metastases and it was observed that the detection of circulating mutant DNA after surgery was highly predictive of disease recurrence [66].…”
Section: Colorectal Cancermentioning
confidence: 98%
“…This is partly due to KRASmutation, which is currently assessed in the primary tumor. Many studies assessed mutation status in circulating tumor DNA, with the aim to improve patient selection [65], [66], [67] and [68].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Detection of mutant KRAS in the blood before surgery predicted recurrence (p < 0.01), but not overall survival. 80 Large prospective trials are needed to confirm the prognosis value of ctDNA. Future studies evaluating post-operative ctDNA levels could generate personalized markers based on the unique mutational profile of resected tumors, offering exquisitely high specificity to predict recurrence and/or evaluate prognosis.…”
Section: Cancer Diagnosis and Screeningmentioning
confidence: 99%
“…[12][13][14] Ki-ras mutations are associated with significantly worse prognosis for the patient. [14][15][16] Likewise, c-Ha-ras encodes the p21c-Ha-ras protein, which induces G 1 cell cycle phase arrest, 17 and c-Ha-ras hypomethylation is detected in gastric carcinomas, though without affecting the histopathologic appearance of the cancers. 18 Finally, increased serum levels of the ERBB2 protein, which is involved in the signal transduction pathways leading to cell growth and differentiation, are common in patients with gastric carcinomas.…”
Section: Mutations and Oncogenesmentioning
confidence: 99%